In the Name of the Spirit - Lynn Briggs; Fred Schunter; Ray Melvin (Journal of the Assembly for Expanded Perspectives on Learning, 2013)
The authors argue that naming experiences "spiritual" is important to an expanded understanding of goals, struggles, and success in their writing center practice.
Keywords: Writers& #x27; Center; International Students; Responders; Listening